Educação infantil na era da técnica: des-caminhos para o poder-ser mais autêntico - Glaser, Priscilla Andrea (2012)
The present research aims do study the meaning of educating for childhood education teachers. To reach this objective, we endeavored to understand the relationship between the meaning of being child and the meaning of educating for childhood education teachers, since these two notions beacon the practice of teaching. To answer this research problem, two groups of childhood education teachers were interviewed: one of a school known as traditional and the other of a so called non-traditional school, through the reflective collective interview. Through this study it becomes evident that depending on the understanding the teacher has of being child directs the way he or she teaches a child and, somehow, facilitates or makes it difficult the being educator. To build on a representational view of child, in which the being of child is found in its fixity, fosters the teacher to believe that the ideal model of teacher exists and to try to possess this model, showing certain automatic movement and feebleness. In addition, the teacher clings to one model of education as being the ideal for every and any child, in which teacher and student have to conform with. Thereby, teacher lives the teaching as a technique to be applied. This situation formed by this way of conceiving the being child, the being educator and the education makes it difficult for the teacher to unhide a meaning of teaching, which he can appropriate in a more authentic manner, as well as for the student, it makes it difficult for him to appropriate of himself. The teacher ends up complying with a scheme, in which the things come already done, following a way of teaching as if it were the only and exclusive manner of teaching. This way of appropriating of teaching can be approximated to a more inauthentic way of being. Regarding the children, a teaching that conceives them in a generalized way and takes care of them in the same manner, ends up not seeing anyone. A teaching that walks for the children, that presents them a finished world which they have to comply with, makes it difficult for them to put their own being in the line and to build themselves along with their world in a more authentic way, pressuring them to stay in the inauthenticity of the they-self . Meanwhile, when the being child is understood as a whole and the time of being child is respected (marked by primacy of the present and the intensity with which her being-in-the-world is being built), fosters the being educator, because it propitiates the teacher to appropriate of the teaching as something in the constant transformation, to look for necessary flexibility to deal with each student in his uniqueness, watch the way the child is showing herself, not tighten up in an only way of understanding and teaching every and any child. As the teacher conceives the child as singular, he considers himself as a craftsman. This way of being educator demonstrates a critical-reflexive posture, that unfolds in the way of leading with the students. It is a teaching that takes place in the meeting between teacher and student and through the dialogue, the poetic language, that promotes in the child a reflexive look at herself and goes in the direction of facilitating the child to take for herself her potentiality-for-being in a more authentic manner, that is, to track and take care of trajectory of being in a more authentic way